2018
DOI: 10.14419/ijet.v7i2.17.11719
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Routing In Wsn Using Enhanced Fuzzy Logic

Abstract: In order to gather info additional precisely, wireless detector networks (WSNs) square measure divided into clusters. The cluster provides a good merit to make longer the period of WSNs. Topical clump comes close to usually use 2 methods: choosing cluster heads with additional enduring energy, and turning cluster heads sporadically, to distribute the energy consumption among nodes in every cluster and extend the network period. However, most of the previous algorithms haven't thought of the expected residual e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…From the Table 7 below can be concluded that Adi has a very good value that is 0.250 followed by Eni with value 0.246, followed by Santi with value 0,230, followed by Tya with value 0,141, and the last is Gita with value 0,133. This research inspired by research related with fuzy logic and artificial intelligence [16] - [61].…”
Section: Performance Appraisal Page Of Employeesmentioning
confidence: 99%
“…From the Table 7 below can be concluded that Adi has a very good value that is 0.250 followed by Eni with value 0.246, followed by Santi with value 0,230, followed by Tya with value 0,141, and the last is Gita with value 0,133. This research inspired by research related with fuzy logic and artificial intelligence [16] - [61].…”
Section: Performance Appraisal Page Of Employeesmentioning
confidence: 99%